The Hidden Costs of Teacher Turnover - Lucy C. Sorensen; Helen F. Ladd (SAGE Publishing, 2020)
High teacher turnover imposes numerous burdens on the schools and districts from which teachers depart. Some of these burdens are explicit and take the form of recruiting, hiring, and training costs. Others are more hidden and take the form of changes to the composition and quality of the teaching staff. This study focuses on the latter. We ask how schools respond to spells of high teacher turnover and assess organizational and human capital effects. Our analysis uses two decades of administrative data on math and English language arts middle school teachers in North Carolina to determine school responses to turnover across different policy environments and macroeconomic climates. Based on models controlling for school contexts and trends, we find that turnover has marked, and lasting, negative consequences for the quality of the instructional staff and student achievement. Our results highlight the need for heightened policy attention to school-specific issues of teacher retention.